Desenvolvimento de biossensor baseado em microcantilever funcionalizado com biomoléculas para a detecção de alcoois de cadeia curta - Margarido, Alexandre (2016)
This study presents the development of a biosensor using a microcantilever stem and its detecting response through dynamic mode of atomic force microscopy (AFM). Responses of different methods for immobilization of alcohol dehydrogenase enzyme were investigated in order to accomplish a selective detection of ethanol, methanol and isopropanol, using as arrays: self-assembly monolayer (SAM) and others arrangements formed on Si and Si3N4 microcantilevers surface. In addition, we aimed to evaluate the influence of the biological element immobilization process in the analytical performance of the biosensor. The process to development of a biosensor began with the activation of its surface by means of thiols and silanes with different carbon length chains, however with the same amine terminal groups (NH2). The microcantilevers activation is only possible with the oxidation of its surface and to check this process, the "High-resolution Xray Photoelectron Spectroscopy (XPS)" technique was used. Activation of the surface was obtained using different methods for coating of microcantilevers made only with Si (100) and Si3N4. Subsequently to the oxidation process, the binding of the biomolecule to the surface activated was performed using the bifunctional agent glutaraldehyde. Microcantilevers with both sides coated by biomolecules were investigated and a tension effect of surface was observed at a 0,3 mL/L of the target analyte. By analyzing the performance of the biosensor for the determination of the target analyte, it was realized that APTES activation methodology for biosensors steam and self-assembled monolayers were the most suitable techniques for immobilizing the recognition biomolecule. With this preparation, the biosensor it showed less susceptible to humidity and the temperature variations, presenting a high quality factor, a faster response time, selectivity, sensitivity and durability.